1996
DOI: 10.1016/0304-3959(95)00169-7
|View full text |Cite
|
Sign up to set email alerts
|

Anger management style, hostility and spouse responses: gender differences in predictors of adjustment among chronic pain patients

Abstract: This study examined whether relationships between anger management style (anger suppression; anger expression) and adjustment variables for patients with chronic pain depend on patient hostility, and/or depend on a patient's gender. A 'spouse response model' was also evaluated to test whether patient expression of hostile anger is linked to infrequent positive and frequent negative responses from spouses, and hence to poor adjustment. The sample of 127 married chronic pain patients was assessed prior to entry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 29 publications
4
98
1
1
Order By: Relevance
“…In contrast, while anger-out was significantly correlated with negative affect in this study, this overlap did not account for its genetically-moderated influence on pain responsiveness. This finding of unique effects of an anger expressive style is supported by several previous studies [7,9,12,14].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, while anger-out was significantly correlated with negative affect in this study, this overlap did not account for its genetically-moderated influence on pain responsiveness. This finding of unique effects of an anger expressive style is supported by several previous studies [7,9,12,14].…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, measures of anger-in and anger-out are associated positively with other measures of general negative affect [4,7,14,43]. It is therefore possible that effects of anger management style, and genetic moderation of those effects, on acute pain responses might not reflect unique effects of anger management style, but rather the effects of shared variance with general negative affect.…”
Section: Discussionmentioning
confidence: 99%
“…In a related fashion, perceived injustice might contribute to poor recovery outcomes by compromising the development of a strong working alliance between the client and the clinician (Burns, Johnson, Mahoney, Devine, & Pawl, 1996;Dahlen & Martin, 2005;Fox, Spector, & Miles, 2001). The working alliance describes warmth, trust, and a shared sense of the presenting problem, solution, and the therapeutic goals between a client and clinician (Corbière, Bisson, Lauzon, & Ricard, 2006;Horvath & Greenberg, 1989).…”
Section: Processes Linking Perceived Injustice To Adverse Pain Outcomesmentioning
confidence: 99%
“…The effectiveness of emotion regulation Coping and emotion regulation have also been considered in the context of gender differences in pain-emotion relations. Burns et al (1996) found that the worst pain severity is reported by women also reporting high hostility and high anger expression, while men with high hostility but low anger expression reported more severe pain. The authors, without proposing a detailed theoretical explanation, related these findings to psychoanalytic literature on anger suppression and research on the social impact of anger expression.…”
Section: Coping and Emotion Regulation -Context-dependence In Chronicmentioning
confidence: 90%
“…Some Running head: DYNAMIC PAIN-EMOTION RELATIONS 32 studies (e.g. Burns et al, 1996) use post-hoc testing to clarify the relations between the predictor and the outcome at different levels of the chosen moderator. Although this analysis is certainly valuable to the interpretation, it does not represent a test of the theoretical decision regarding which variable represents the moderator.…”
Section: ______________________mentioning
confidence: 99%